Occurrence of Antimicrobial Resistance in Canine and Feline Bacterial Pathogens in Germany under the Impact of the TÄHAV Amendment in 2018 - Marianne Moerer; Antina Lübke-Becker; Astrid Bethe; Roswitha Merle; Wolfgang Bäumer (Antibiotics, 2023)
The occurrence of antimicrobial resistance due to the use of antimicrobials is considered to be a main cause for treatment failure of bacterial infections in humans and animals. The right of German veterinarians to use and prescribe medications such as antimicrobials is regulated by the Regulation of Veterinary Pharmacies (TÄHAV). The aim of this study was to investigate the impact of the second amendment to the TÄHAV in 2018 on the occurrence of antimicrobial resistance in selected bacterial pathogens isolated from dogs and cats in Germany. For this purpose, we analyzed antimicrobial susceptibility data from 38 German small animal practices gathered between 2015 and 2021 in cooperation with Laboklin (Labor für klinische Diagnostik GmbH & Co.KG, Bad Kissingen, Germany). Annual cumulative susceptibility data of eight bacterial species were analyzed and compared. The mean value of resistant isolates was determined for each year and supplemented by 95% confidence intervals. Encouraged by the amendment, an increase in sample submissions was observed in Germany. The highest resistance rates to the analyzed substances penicillin G, ampicillin, amoxicillin-clavulanic acid, cefovecin, and enrofloxacin were found for Staphylococcus pseudintermedius (S. pseudintermedius), S. aureus, and Escherichia coli (E. coli). In contrast, resistance rates were low for Pasteurella multocida (P. multocida) and β-hemolytic streptococci. Significant resistance trends (p < 0.05) assumed as influenced by the TÄHAV amendment could be the significant decreases in resistance rates of S. pseudintermedius against penicillin G to 67% (n = 322/479), and ampicillin to 63% (n = 286/453), as well as S. felis against amoxicillin-clavulanic acid and cefovecin to 2% (n = 2/109), furthermore, the reduction in the occurrence of resistance of S. aureus against enrofloxacin to 4% (n = 3/76) in 2021. Moreover, for all species, the efficacy against the analyzed substances was maintained over the study period.